Review of the Fund's Income Position for FY 2010 and FY 2011. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Securing the recovery. The global recovery has been better than expected. The WEO projections see global output expanding by about 4u percent in 2010 and 2011. Extraordinary and coordinated policy intervention since the crisis has all but eliminated the risk of another Great Depression, laying the foundation for recovery. Nevertheless, the recovery is proceeding at varying speeds-it is tepid and policy-dependent in many advanced economies, but solid in most emerging and developing economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Gold Profits; Income; Net; PP; Proceeds; United States